Hantavirus infection with pulmonary symptoms in north central part of Sri Lanka - Rohitha Muthugala (Elsevier, 2021)
Background: Classical hantavirus infections present as haemorrhagic fever with renal syndrome (HFRS) in Euro-Asia and as hantavirus pulmonary syndrome (HPS) in America.  Mixed clinical features have been reported from certain novel hantavirus infections. In the north-central part of Sri Lanka, clusters of patients with fever and non-cardiogenic pulmonary edema have been reported in recent years. Objectives: To detect hantavirus infection among clinically suspected patients and to describe clinical and demographic features of hantavirus infection in north-central Sri Lanka. Study design: Clinically suspected patients with HFRS and HPS like illness admitted to two leading hospitals in the north-central part of the country from December 2013 to November 2015 and from March 2016 to February 2018 were included in the study. Acute phase blood samples were tested for the presence of anti-hantavirus IgM. Convalescent blood samples were taken from available cases and both acute and convalescent sera were subjected to IgG titre detection. Results: Seventy-two patients were included in the study.  Twenty-nine (40.28%) were positive for hantavirus IgM. Of them, 20 (68.97%) presented with pulmonary symptoms with no or mild nephritis. Five (17.24%) had pulmonary symptoms with prominent nephritis and 04 (13.79%) had classic features of HFRS. Conclusion: In the north-central part of Sri Lanka, most hantavirus infection was associated with pulmonary symptoms complicated with non-cardiogenic pulmonary edema, which was different from clinical presentation reported previously from other parts of the country. HPS like hantavirus infection in the study area could be due to a Puumala-like virus or a novel virus.